FOSTERING RURAL AGROTOURISM DEVELOPMENT THROUGH SOCIAL ENTREPRENEURSHIP AND INNOVATIVE DIGITAL MARKETING PLATFORMS - Rebecha Prananta; Nong Chai; Michael Turner; Margaretta Andini Nugroho (Yayasan Adra Karima Hubbi, 2026)
Rural agrotourism has emerged as a strategic approach for promoting sustainable rural development by integrating agricultural resources, cultural heritage, and tourism activities. Increasing competition within the tourism sector, combined with rapid digital transformation and evolving visitor expectations, has created new challenges and opportunities for rural destinations. Social entrepreneurship offers a promising mechanism for empowering local communities, generating social value, and fostering innovation, while digital marketing platforms provide effective tools for expanding market reach and enhancing destination visibility. This study aims to examine the role of social entrepreneurship and innovative digital marketing platforms in fostering rural agrotourism development and to explore how their integration contributes to sustainable tourism growth. A qualitative research design employing a multiple-case study approach was utilized. Data were collected through the analysis of scholarly literature, institutional reports, tourism development documents, and case-based evidence related to rural tourism enterprises and community-based initiatives. Findings indicate that social entrepreneurship strengthens community participation, enhances local capacity, and promotes destination innovation. Innovative digital marketing platforms, including social media, online promotion tools, and digital storytelling strategies, significantly improve destination visibility, tourist engagement, and market accessibility. Synergistic interaction between entrepreneurial leadership and digital innovation emerged as a critical factor supporting sustainable agrotourism development. The study concludes that integrating social entrepreneurship with digital marketing strategies provides an effective pathway for strengthening rural economies, enhancing tourism competitiveness, and promoting inclusive and sustainable community development.